آراء النظرية البنائية في تعلّم اللغة الثانية والاستفادة منها في تعليم اللغة العربية لغير الناطقين بها - Neneng Sulaila (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
This study used a descriptive analytical approach to constructivism theory in learning a second language and used it in teaching Arabic to non-Arabic speakers by making literature study as a source of data collection. The results of the study showed that (a) The theory of constructivism was the philosophy of education which said that students develop their own knowledge that he keeps in his mind, so learning is an ongoing process. (b) Based on the principle of internal mental processes that occur in the student's brain so that they link past knowledge and present knowledge with the construction of learning activities that produce meaning. (c) The process of learning Arabic occurs after the information is constructed from the process of listening, speaking or writing in accordance with the rules of Arabic, and incorporating the knowledge gained from past knowledge that is influenced by the environment. (d) Learning in constructivism theory is based on four phases: (1) Advocacy (2) Exploration (3) Proposing interpretations and solutions (4) Taking action. (e) Applying constructivism theory in teaching Arabic to non-Arabic speakers based on the principles established by active students in constructing their linguistic knowledge.